(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The lecturer portal at XYZ University is used to support lecturer activities at a university. The purpose of this paper is to test the usability of the information system on the XYZ University lecturer portal whether it is in accordance with the acceptability criteria of usability testing. The test method uses Nielsen’s heuristic evaluation with Nielsen’s ten principles. The high level of popularity and use of the system by users to help them is related to the high level of usability. The test involved 5 evaluators who acted as idea givers, critics and evaluators from 10 aspects of usability as material for analysis. The results of the analysis show that there are independent variables that have a dominant influence on the usability of the application, namely the visibility of the system variable, the recognition rather than recall variable, the error prevention variable, the flexibility and efficiency of use variable and the help and documentation variable. The results showed that the questionnaire index value of the XYZ University lecturer portal information system has a severity rating of 0.67, which means that the problem does not have to be fixed directly, but can be fixed when there is development.